2020
DOI: 10.3390/ijms21249600
|View full text |Cite
|
Sign up to set email alerts
|

Increased miR-142 Levels in Plasma and Atherosclerotic Plaques from Peripheral Artery Disease Patients with Post-Surgery Cardiovascular Events

Abstract: There is an intensive effort to identify biomarkers to predict cardiovascular disease evolution. We aimed to determine the potential of microRNAs to predict the appearance of cardiovascular events (CVEs) in patients with peripheral artery disease (PAD) following femoral artery bypass surgery. Forty-seven PAD patients were enrolled and divided into two groups, without CVEs (n = 35) and with CVEs (n = 12), during 1 year follow-up. Intra-surgery atherosclerotic plaques from femoral arteries were collected and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…miR-142-3p, known to be involved in atherosclerosis [ 55 ] and ischemic heart disease [ 35 ] proved to be an independent prognostic marker of adverse outcome in our group of young patients with STEMI. Its prognostic value was tested using an ROC curve analysis, where we obtained an AUC of 0.732 (95% CI), p = 0.031, and determined an optimal cut-off value of 1115 (sensitivity 77.8%, specificity 68.3%) for MACE prediction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…miR-142-3p, known to be involved in atherosclerosis [ 55 ] and ischemic heart disease [ 35 ] proved to be an independent prognostic marker of adverse outcome in our group of young patients with STEMI. Its prognostic value was tested using an ROC curve analysis, where we obtained an AUC of 0.732 (95% CI), p = 0.031, and determined an optimal cut-off value of 1115 (sensitivity 77.8%, specificity 68.3%) for MACE prediction.…”
Section: Discussionmentioning
confidence: 96%
“…The data were analysed using ViiA7 Software v1.2 with the automatic Cq setting. The expression level of each miRNA was determined relative to that of exogenously added cel-miR-39-2p (ID 000200) as previously reported [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, upregulated miR-92a is considered as a differential biomarker for UA [144]. However, miR-92a expression decreased in the blood of patients with CAD [108,111,154], CHD [112] and atherosclerosis [155], in plasma and atherosclerotic plaques in PAD patients with cardiovascular events (CVEs) [156].…”
Section: Mir-92a Abca1mentioning
confidence: 99%
“…In THP-1 macrophages, miR-212 targeted SIRT1, which led to inhibition of ABCA1 expression, decreased cholesterol efflux and increased intracellular lipid accumulation [190]. [191], in serum, in the vascular wall of patients with atherosclerosis obliterans [192], in the plasma of patients with AMI [115], PAD with cardiovascular events (CVEs) [156], unstable coronary artery disease (UCAD) [193], coronary artery calcification (CAC) [194] and UA [99,105], in platelets of patients with CAD [195], in atherosclerotic plaques of patients with PAD with cardiovascular events (CVEs) [156], and in aneurysm tissues of patients with AAA [119]. HDL-transported miR-223 elevated in patients with hypercholesterolemia and in Ldlr −/− and ApoE −/− mice on a high-fat diet.…”
Section: Mir-185 Scarb1mentioning
confidence: 99%
“…Many studies have indicated an important role of miRNAs in vascular pathology [ 25 , 26 , 27 , 28 ] and have pointed to certain dysregulated miRNAs as candidates for biomarkers of LEAD [ 29 , 30 ], AAA [ 31 ], and CVD [ 32 , 33 , 34 ]. Special attention is paid to the identification of circulatory miRNA biomarkers (from whole blood, blood cells, plasma, or serum) with potential utility as diagnostic, prognostic, and therapeutic targets for these diseases [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%